2020
DOI: 10.1152/ajpheart.00629.2019
|View full text |Cite
|
Sign up to set email alerts
|

PKCβ and reactive oxygen species mediate enhanced pulmonary vasoconstrictor reactivity following chronic hypoxia in neonatal rats

Abstract: Reactive oxygen species (ROS), mitochondrial dysfunction, and excessive vasoconstriction are important contributors to chronic hypoxia (CH)-induced neonatal pulmonary hypertension. On the basis of evidence that PKCβ and mitochondrial oxidative stress are involved in several cardiovascular and metabolic disorders, we hypothesized that PKCβ and mitochondrial ROS (mitoROS) signaling contribute to enhanced pulmonary vasoconstriction in neonatal rats exposed to CH. To test this hypothesis, we examined effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 68 publications
2
7
0
Order By: Relevance
“…MitoSOX fluorescence intensity in hypoxic HPASMCs was increased, which was decreased after C75 incubation or shFAS infection (Figures 7(d) and 7(e) ). This is in line with the latest reports; Sheak et al reported PKC β and mitochondrial reactive oxygen species signaling to increase pulmonary vasoconstrictor reactivity in chronically hypoxic neonates [ 22 ]. Hang et al reported that hypoxia increased BPA levels of MitoSOX-detected superoxide and caused changes in NOX2 and SOD2 expression similar to COMP siRNA, and exogenous COMP (0.5 μ M) prevented the effects of hypoxia [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…MitoSOX fluorescence intensity in hypoxic HPASMCs was increased, which was decreased after C75 incubation or shFAS infection (Figures 7(d) and 7(e) ). This is in line with the latest reports; Sheak et al reported PKC β and mitochondrial reactive oxygen species signaling to increase pulmonary vasoconstrictor reactivity in chronically hypoxic neonates [ 22 ]. Hang et al reported that hypoxia increased BPA levels of MitoSOX-detected superoxide and caused changes in NOX2 and SOD2 expression similar to COMP siRNA, and exogenous COMP (0.5 μ M) prevented the effects of hypoxia [ 23 ].…”
Section: Discussionsupporting
confidence: 92%
“…Protein kinase C β (PRKCB) was also increased in individuals with higher DNA damage. ROS production is stimulated by PRKCB, thus leading to an increase in DNA damage, which can explain the association found in this study [ 68 , 69 ]. Others have demonstrated that PRKCB regulates cellular signaling pathways involved in the autophagic process [ 43 ].…”
Section: Discussionsupporting
confidence: 60%
“…We find that in our case population, the risk-associated SNP found in PRKCB was found in 165 severe COVID-19 cases (penetrance = 20.2%), and was present in 45% of patients with cardiovascular disease and 51% of patients with hypertension. High levels of PKCβ result in increased vascular inflammation, endothelial dysfunction and oxidative stress, all of which have been found in patients with severe COVID-19 92,93 .…”
Section: Discussionmentioning
confidence: 99%